Pengaruh Motivasi Diri, Efikasi Diri dan Penggunaan Teknologi terhadap Kepuasan Kerja - Kristiyana, Naning; Cendriono, Nanang; Hamidah, Choirul (ASSET: Jurnal Manajemen dan Bisnis, 2023)
This study aims to examine the variables of job satisfaction which are influenced by self-motivation, self-efficacy, and use of technology factors. The objects in this study were employees of BUMN Madiun. The population is company employees who are in middle management by taking the saturated sample method. The results of this study indicate that only the use of technology factor has an effect on employee job satisfaction, while the self motivation and self efficacy factors have no effect on employee job satisfaction.